Persistent infantile mastocytosis with small monomorphous lesions. - Bonifazi, E.; Garofalo, L. (European Journal of Pediatric Dermatology, 2009)
Almost all the cases of mastocytosis started in the first year regress spontaneously within about ten years as well as infantile hemangioma. Is it not possible to foresee the lack of regression in those few cases in which the lesions persist unchanged after puberty. As serum triptase is expression of the burden of mastocytes in the body, its dosage could be used to foresee the regression of mastocytosis. However, there are not prospective studies on this topic. Moreover, the level of triptase is not usually increased in exclusively cutaneous mastocytosis, which is characteristic of childhood (2). In the case here reported the late onset and the monomorphous lesions, which are typical of adults, could be considered as possible indicators of persistence. A more important indicator could be the non-rarefaction of the swelling episodes.